1995
DOI: 10.1136/jcp.48.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 in idiopathic pulmonary fibrosis.

Abstract: Aims-To evaluate whether endothelin-1 is involved in the pathology of idiopathic pulmonary fibrosis (IPF). Methods-Plasma endothelin-1 concentrations were evaluated in 37 patients with IPF and 27 normal controls by radioimmunoassay. In addition, expression of endothelin-1 in lung tissue was evaluated in biopsy specimens obtained from four patients with IPF. Three biopsy specimens of normal lung were used as controls. Endothelin-1 immunoreactivity was detected using immunohistochemistry. Results-Elevated endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 28 publications
(4 reference statements)
6
66
0
1
Order By: Relevance
“…We observed a marked thickening of the alveolar wall and a corresponding reduction in ET-1 staining intensity after the peak increase in ET-1 levels in tissue extracts. Uguccioni et al reported that ET-1 might play a role in the fibrogenic process of idiopathic pulmonary fibrosis (IPF) [14]. The histological evidence of IPF resembles the pulmonary lesions observed in this study, thus suggesting the fibrogenic process of ET-1 in the course of GVHD.…”
Section: Discussionsupporting
confidence: 82%
“…We observed a marked thickening of the alveolar wall and a corresponding reduction in ET-1 staining intensity after the peak increase in ET-1 levels in tissue extracts. Uguccioni et al reported that ET-1 might play a role in the fibrogenic process of idiopathic pulmonary fibrosis (IPF) [14]. The histological evidence of IPF resembles the pulmonary lesions observed in this study, thus suggesting the fibrogenic process of ET-1 in the course of GVHD.…”
Section: Discussionsupporting
confidence: 82%
“…28,29 ET-1 is normally produced by endothelial cells, but it has been shown also to be overexpressed by fibroblasts in certain fibrotic conditions, including scleroderma and idiopathic pulmonary fibrosis. 30 Recent reports, including our own work, have shown that ET-1 expression is highly induced by TGF-b1 stimulation, and like TGF-b1, ET-1 has been described to promote the epithelial-to-mesenchymal transition.…”
mentioning
confidence: 99%
“…There is now substantial evidence to support the notion that ET has mitogenic effects on fibroblasts, reduces collagen breakdown and induces the synthesis of ECM components, all contributing to fibrosis [10]. ET has been detected in the plasma of patients with IPF at significantly higher levels compared with matched controls (p,0.01) [11] and in patients with scleroderma, levels of ET in bronchoalveolar lavage fluid are higher in patients with lung fibrosis than in patients without lung involvement ( fig. 4) [12].…”
Section: Rationale For Using Endothelin Receptor Antagonists In Ipfmentioning
confidence: 83%